2012
DOI: 10.1038/ijo.2011.263
|View full text |Cite
|
Sign up to set email alerts
|

History matters: childhood weight trajectories as a basis for planning community-based obesity prevention to adolescents

Abstract: OBJECTIVE: To use epidemiological data and a standardized economic model to compare projected costs for obesity prevention in late adolescence accrued using a cross-sectional weight classification for selecting adolescents at age 15 years compared with a longitudinal classification. METHODS: All children born in a Swedish county (population 440 000) in 1991 who participated in all regular measurements of height and weight at ages 5, 10 and 15 years (n ¼ 4312) were included in the study. The selection strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Intervening during this critical time period has the potential to prevent the development of CVD risk in adolescence, which has implications for reducing the incidence of adult chronic illness. 36,37 …”
Section: Discussionmentioning
confidence: 99%
“…Intervening during this critical time period has the potential to prevent the development of CVD risk in adolescence, which has implications for reducing the incidence of adult chronic illness. 36,37 …”
Section: Discussionmentioning
confidence: 99%
“…Enhanced knowledge of the dynamics of BMI change across the life course, especially the development of pathologic versus normal age-related BMI trajectories, may help guide clinical and public health practice by suggesting critical and sensitive windows for intervention targeted at reducing the incidence of adult obesity with the aim of halting the progression of existing obesity. 26,56,57 This is the first study in which researchers describe BMI patterns from early childhood to midadulthood in 4 groups of clinical interest. A better understanding of the trajectories of those who develop obesity or those who had high BMI in childhood but did not become obese in adulthood is particularly important from a public health perspective.…”
Section: Figurementioning
confidence: 99%
“…The study was performed in a health care region (population 1 200 000) in the south east of Sweden, where analyses of obesity data had shown that the need for obesity prevention among adolescents was greater than the resources available [20]. The results indicated that obese adolescents would benefit from more specialized interventions; a need for an online public health intervention addressing the non-obese adolescent population was also identified.…”
Section: Introductionmentioning
confidence: 99%